The Acetyltransferase RibT From Bacillus subtilis Affects in vivo Dynamics of the Multimeric Heavy Riboflavin Synthase Complex - Rotter, Daniel Andreas Orlando; Heger, Christoph; Kühm, Christian; Schmidt, Nina; Schäfer, Antje; Heimerl, Thomas; Mack, Matthias; Graumann, Peter L. (Frontiers in Microbiology, 2022)
Flavins are ubiquitous molecules in life as they serve as important enzyme cofactors. In the Gram positive, soil dwelling bacterium Bacillus subtilis four well characterized gene products (the enzymes RibDG, RibE, RibAB and RibH) catalyze the biosynthesis of riboflavin (RF) from guanosine-triphosphate (GTP) and ribulose 5 phosphate (R5P). The corresponding genes form an operon together with the gene ribT (ribDG E AB H T), wherein the function of this terminal gene remained enigmatic. RibT has been structurally characterized as a GCN5 like acetyltransferase (GNAT), however with unidentified target molecules (Srivastava et al., 2018). Bacterial two hybrid system revealed interactions between RibT, RibH and RibE, forming the heavy RF synthase complex. Applying single particle tracking (SPT) we found that confined (sub)diffusion of RibT is largely dependent on interacting RibE and to a lesser degree on interacting RibH. By induced expression of otherwise low-expressed ribT from an ectopic locus, we observed a decrease in the subpopulation considered to represent capsids of the heavy RF synthase and an increase in the subpopulation thought to represent pentamers of RibH, pointing to a putative role for RibT in capsid disassembly. Complementary, either deletion of ribT or mutation of a key residue from RibH (K29) suspected to be the substrate of RibT for acetylation, lead to increased levels of subpopulations considered as capsids of RibH mVenus (RibH mV) in comparison to wild type (wt) like cells. Thus, we provide evidence for an indirect involvement of RibT in RF biosynthesis by a putative capsid disassembling mechanism considered to involve acetylation of RibH residue K29 at the threefold symmetry axis of 60 mer capsids.